The middle muddle: Conceptualizing and measuring the global middle class - Arjun Jayadev; Rahul Lahoti; Sanjay Reddy (Georg-August-Universität Göttingen, Courant Research Centre - Poverty, Equity and Growth (CRC-PEG), 2015)
Interest in the emergence of a global middle class has resulted in a number of attempts to identify and enumerate who belongs to it . Current research provides wildly different estimates about the size and evolution of the global middle class because of a lack of consensus on appropriate identification criteria for a person to be deemed to be middle class. We identify three competing and often conflated understandings in the literature on the subject. We further argue that for at least two of these understandings, the literature has been using inappropriate thresholds for identification. Using data from the Global Consumption and Income Project, we provide estimates of the size, composition and evolution of the global middle class for three competing understandings and contrast these to existing estimates.
Keywords: D30; D31; D60; D63; E21; O50; O10; 330